ANALISIS PENGENDALIAN LAJU KOROSI DAN SISA UMUR PAKAI PIPA PENYALUR SOLAR DI PLTD HARUKU, DESA PELAUW - Husen, Fahmi; Karyani, M. Said; Pellu, Deny Ismail (Journal Mechanical Engineering, 2024)
The impact of the corrosion rate of diesel fuel pipes in PLTD HARUKU, DESA PELAUW. This study aims to see how much influence corrosion control has on the corrosion rate and remaining service life studied using an Ultrasonic Thickness Gauge. Measurements were carried out directly with an Ultrasonic Thickness Gauge. The measurement results showed that the highest corrosion rate was 0.0975 mmpy and the lowest was 0.0189. The remaining life of each pipe is determined by a formula that has been adjusted by the standard, with a higher corrosion rate causing a shorter pipe life, in the diesel fuel pipe the highest remaining service life of the IPA is 149 years due to the small corrosion rate while the pipe with the lowest service life is 25 years due to the high corrosion rate. Based on this analysis, the pipe is still feasible to operate. In conclusion, although there are variations in the corrosion rate, and the remaining service life of the pipe can still be operated safely. Keywords: Corrosion control, Corrosion, ultrasonic thickness gauge